EXOGENOUS APPLICATION OF ABSCISIC ACID FOR DROUGHT TOLERANCE IN SUNFLOWER (HELIANTHUS ANNUUS L.): A REVIEW - S. Hussain; A. Ali; M. Ibrahim; M. F. Saleem; M. A. alias Haji A. Bukhsh (Journal of Animal and Plant Sciences, 2012)
Sunflower has been successfully cultivated over a widely scattered geographical area in the world and also emerged as a crop, which has ability to adopt in a variety of environmental conditions. Sunflower is high yielding oilseed crop and has the potential to bridge up the gap existing between consumption and domestic production of edible oil. Water is essential at every stage of plant growth and development. Water deficit reduces crop yield regardless of the growth stage at which it occurs in field crops including sunflower. The productivity and spatial distribution of agronomic and horticultural crop plants of commercial importance are severely restricted by a variety of environmental factors. Among these factors, drought and salt play very significant role in reducing agricultural production. Water deficit effect is much pronounced at the vegetative and flowering stage. In sunflower water shortage at the flowering stage reduced yield by 29 %. Dwarf cultivars of sunflower have higher water potential i.e. least water stress as compared to intermediate and long stature cultivars. This is due to difference in canopy architecture and root penetration depth among different stature sunflower cultivars. Tall stature cultivars produced more leaf area, aerial biomass and deeper root system so they transpired more water. Major effect of drought in plant is reduction in photosynthesis, which is due to decrease in leaf expansion, impaired photosynthetic machinery, leaf senescence and finally reduction in assimilates production and partitioning. Sunflower exhibits a large varietal difference for osmotic adjustment in response to water shortage. Drought tolerance has been observed in all plant species, but its extent varies from species to species. One way to ensure future food needs of the increasing world populations should involve better use of water by the development of crop varieties those require lesser amounts of water and more tolerant to water shortage. Water deficit in root zone causes an increase in rate of root respiration which leads to an imbalance in the utilization of carbon resources, decrease in production of adenosine triple phosphate (ATP) and an increase in production of reactive oxygen species (ROS). Genotypic variation for osmotic adjustment has also been reported in sunflower. The dwarf sunflower cultivars have initiated osmotic adjustment earlier than intermediate and large stature cultivars which indicated better osmotic response of dwarf cultivars. The delay in osmotic adjustment in intermediate and tall stature sunflower genotypes is due to faster root penetration and more water extraction from deeper layer of soil. So, tall stature sunflower cultivars face water stress later as compared to short stature. Three growth stages of sunflower as heading, flowering and milking are sensitive to water shortage. In limited irrigation application study, water applied at different growth stages of sunflower significantly decreased seed yield, particularly during three growth periods: heading, flowering and milking. The role of abscisic acid (ABA) as plant stress hormone is well established. Under drought condition, ABA is synthesized in plant tissue and sent to the guard cell as a stress signal. Here ABA causes stomatal closure, which improves the water relations of plant. ABA entering a leaf can be metabolized rapidly. In response of water deficit, ABA begins to increase markedly in plant leaf tissues and to a lesser extent, in other tissues including roots. This leads to stomatal closure and decreased transpiration. It also inhibits shoot growth and root growth appears to be promoted which increased the water supply. It helps in promoting drought tolerance, both from the use of exogenous application to intact plants and from the measurement of the endogenous ABA concentration. In response to exogenous application of ABA in drought tolerant line of sunflower dehydrin protein accumulated in vegetative tissue. Dehydrin protects cytosolic structures from the deleterious effects of cellular dehydration. ABA plays a critical role in regulating plant water status through guard cells and growth as well as by induction of genes that encode enzymes and other proteins which create cellular dehydration tolerance. In plants stomata response to soil drying is mediated by ABA, originating from roots and transported to the shoot via the transpiration stream. ABA under drought is produced in dehydrated roots, transported to the xylem and regulates stomatal opening and leaf growth in the shoots. Stomata respond to the concentration of ABA in the guard cell apoplast. Screening of sunflower cultivars under drought applied at different crop growth stages and exogenous application of ABA will defiantly help in saving water for successful crop production.
Keywords: Sunflower cultivars; drought; growth stages; ABA application